Absolute beginning : ensaio sobre a emergência do rock'n'roll - Guerra, Paula (2015)
Rock became, from the mid-twentieth century, a worldwide language. It is present through sounds, images and texts on everyday of the population, and has become a global mediascape. Despite this centrality and importance in the structuring of popular culture, rock has been the subject of a relative devaluation as standard and culture matrix. Thus, the text presented intends to reveal the importance of rock, discovering its potential of dialogue and cross with the legitimate discourse of school and science about popular cultures. This ambulation shows, then, how rock was an absolute beginner because it changed, in its expressiveness, the cultural patterns, cultural industry, youth practices, artistic creations and artistic manifestations in public spaces. We assume that music is the transposition of the principles and structural properties of social life, and then it can be a matrix that has shaped new subjectivities, metamorphosing the everyday.